Penyelesaian Hukum Kredit Macet Akibat Pandemi Covid-19 Di PT. Finansia Multi Finance (Kredit plus) Perspektif Hukum Perdata Indonesia - Didin Saprudin; Lalu Hadi Adha; Mohammad Irfan (Private Law, 2023)
This study aims to explain the legal settlement of bad loans due to the Covid-19 pandemic from the perspective of Indonesian civil law and efforts can be made by PT Finansia Multi Finance (Kredit plus) due to defaults. This research uses a type of normative research that uses a statutory approach and a conceptual approach. The results of the study determined that there are two ways of resolving disputes concerning bad loans, namely litigation, and non-litigation. If these methods cannot achieve a win-win solution or a solution that takes into account both parties, the judge must make a verdict to decide the winning party and the losing party. Dispute settlement has had a strong legal basis since the issuance of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution.